Internet use, eHealth literacy and fear of COVID-19 among nursing students in the Philippines; Uso de Internet y la alfabetización en eSalud con temor al COVID-19 entre estudiantes de enfermería en Filipinas - Ryan Michael Oducado; Cyruz Tuppal; Homelo Estoque; Jonaid Sadang; Daryl Superio; Don Vicente Real; Mary Nellie Roa; Xerxes Malaga; Jejomar Quiros; Maria Teresa Fajardo; Ronnell Dela Rosa (International Journal of Educational Research and Innovation, 2021)
The COVID-19 outbreak brought into focus not only the safety but also the mental well-being of nursing students. At present, the level of fear of COVID-19 and associated factors among nursing students in the Philippines are not well understood. This cross-sectional online survey determined the relationship between Internet use and eHealth literacy with fear of COVID-19. One thousand three hundred and sixty-seven (n=1,367) answered an online survey using the adopted eHealth Literacy Scale (eHEALS), and Fear of COVID-19 Scale (FCV-19S) administered from May 1 to 15, 2020. Descriptive statistics, tests for differences, and correlational analysis were performed. Results indicated that the composite score of the FCV-19S was 3.65, indicating moderate to high levels of fear. Fear of COVID-19 significantly differed based on sex, year level, and location. A significant inverse relationship was found between the average daily use of the Internet and fear of COVID-19. On the other hand, no significant association was noted between eHealth literacy and fear of COVID-19. The first wave of the COVID-19 outbreak has resulted in a far-reaching impact on nursing students' psychological well-being. This study highlights the value of the Internet and its use during the outbreak may not always lead to higher fear related to COVID-19. Nursing schools may need to create strategies to promote regulated and responsible Internet use, address students' mental health concerns, and develop interventions to respond proactively to mitigate or reduce fear among nursing students during the pandemic. – – El brote de COVID-19 puso de relieve no solo la seguridad sino también el bienestar mental de los estudiantes de enfermería. En la actualidad, no se comprende bien el nivel de miedo al COVID-19 y los factores asociados entre los estudiantes de enfermería en Filipinas. Esta encuesta transversal en línea determinó la relación entre el uso de Internet y la alfabetización en eSalud con el miedo al COVID-19. Mil trescientos sesenta y siete (n = 1.367) respondieron una encuesta en línea utilizando la Escala de alfabetización en salud electrónica (eHEALS) y la Escala de miedo a COVID-19 (FCV-19S) administradas del 1 al 15 de mayo de 2020. Estadísticas descriptivas, se realizaron pruebas de diferencias y análisis correlacional. Los resultados indicaron que la puntuación compuesta del FCV-19S fue de 3,65, lo que indica niveles de miedo de moderados a altos. El miedo al COVID-19 difirió significativamente según el sexo, el a\~no y la ubicación. Se encontró una relación inversa significativa entre el uso diario promedio de Internet y el miedo al COVID-19. Por otro lado, no se observó una asociación significativa entre la alfabetización en eSalud y el miedo al COVID-19. La primera ola del brote de COVID-19 ha tenido un impacto de gran alcance en el bienestar psicológico de los estudiantes de enfermería. Este estudio destaca el valor de Internet y su uso durante el brote no siempre puede generar un mayor temor relacionado con el COVID-19. Las escuelas de enfermería pueden necesitar crear estrategias para promover el uso de Internet regulado y responsable, abordar las preocupaciones de salud mental de los estudiantes y desarrollar intervenciones para responder de manera proactiva para mitigar o reducir el miedo entre los estudiantes de enfermería durante la pandemia.
Keywords: 330; COVID-19; Internet; eHealth literacy; electronic health literacy; fear; coronavirus; students; nursing